Cost-effective Ultrasonic Extraction of Bioactive Polyphenols from Vine and Wine Waste in Serbia - Radovanović, V.N; Andjelković, M.; Arsić, B.; Radovanović, A.; Gojković-Bukarica, L. (South African Journal of Enology and Viticulture, 2019)
By using cost-effective ultrasonic extraction techniques, bioactive phenolic extracts were obtained from Merlot and Vranac (Vitis vinifera L.) vine and wine waste produced in Serbian wineries. These wastes include vine leaves, grape pomace, seeds, skins and stems, which can find further use in the food and pharmacology industries as preservatives against microbes. The extracts showed strong scavenging free radical activity (EC50 from 0.37 to 2.02 mg/L), which was in very good correlation with the total polyphenol content. Strong antimicrobial activity was found against six Gram-positive and five Gram-negative bacterial strains, and against the yeast Candida albicans. The principal component and agglomerative hierarchical clustering analyses performed were shown to be good for grouping and distinguishing the results from the vine and wine by-products (leaves and seeds) from both investigated grape varieties based on the content of various polyphenolic classes, and antioxidant and antimicrobial activities. The valorisation of the grape by-products is consistent with the concept of a sustainable and environmentally oriented wine industry and provides an important economic advantage.